Taxa de coinfecção viral em crianças e adolescentes internados pelo Sarscov-2: características clínicas e epidemiológicas - Bezerra, Lua Flora Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Introduction: Infection by coronavirus 2 (Sars-CoV-2), a new virus identified in late 2019 in China, spread worldwide in early 2020 and studies have shown that the pediatric population was less affected, representing 1-5% of total cases. Children also tend to be asymptomatic or develop mild symptoms, consisting of: fever, cough and runny nose, symptoms that make it difficult to differentiate children infected by SarsCoV-2 from those infected by other viruses that commonly affect them. No clinical or radiological findings allow us to rule out infection by other more common viruses, which can cause underdiagnosis of the disease. Objectives: The present study aimed to identify the prevalence of respiratory co-infection by the Sars-CoV-2 virus with Respiratory Syncytial Virus and/or Influenza A or B and to compare the clinical and epidemiological characteristics between the isolated infection group and the coinfected group. As well as the creation of a viral testing protocol. Methods: The medical records of 116 patients admitted to the wards and pediatric ICU of HCFMB from March 2021 to July 2022 were analyzed. This is an observational study with retrospective data collection. Statistical analysis of the data was performed and the results presented in the form of tables and graphs. Results: 116 patients eligible for the study with confirmed Sars-CoV-2 infection were analyzed. Of these, only 4 were co-infected, 3 by RSV and 1 by Influenza B. The most prevalent clinical signs and symptoms in patients with co-infection were: dyspnea, fever, respiratory distress, presence of retractions and crackles on pulmonary auscultation, which were equally prevalent. In patients who had only Sars-CoV-2 infection. In the group with viral co-infection, a longer time on oxygen therapy was observed, as well as a higher rate of radiological and/or hematological alterations, longer hospital stay and need for a therapy unit. Conclusion: Infection by Sars-CoV-2 in children is extremely important and the rate of co-infection with other viruses presents different prevalences depending on the region studied. Due to the low rate of co-infection found in our sample, it was not possible to perform a more detailed statistical analysis, and larger studies with broader viral testing are necessary to better define the impact of co-infection of Sars-CoV-2 with other viruses on the epidemiology and clinical features of these patients.

A infecção pelo coronavírus 2 (Sars-CoV-2), um novo vírus identificado no final de 2019 na China, se espalhou pelo mundo no início de 2020 e estudos demonstraram que a população pediátrica foi menos afetada, representando 1-5% do total de casos; as crianças também tendem a ser assintomáticas ou evoluir com quadros brandos, compostos por febre, tosse e coriza, sintomas que tornam difícil diferenciar a criança infectada pelo Sars-CoV-2 daquelas infectadas por outros vírus que comumente as acometem, não havendo achados clínicos ou radiológicos capazes de afastar a infecção por outros vírus mais comuns, o que pode causar subdiagnóstico da doença. O presente estudo objetivou identificar a prevalência de coinfecção respiratória pelo vírus Sars-CoV-2 com Vírus Sincicial Respiratório e/ou Influenza A ou B e comparar as características clínicas e epidemiológicas entre o grupo de infecção isolada e o grupo de coinfectados, bem como propor a criação de protocolo de testagem viral. Foram analisados os prontuários de 116 pacientes internados nas enfermarias e UTI pediátrica do HCFMB no período de março de 2021 a julho de 2022, em um estudo observacional com coleta de dados retrospectivos, cuja análise estatística foi realizada e os resultados apresentados em forma de tabelas e gráficos. Dos 116 pacientes elegíveis com infecção confirmada pelo Sars-CoV-2, apenas 4 foram coinfectados, sendo 3 por VSR e 1 por Influenza B; os sinais clínicos e sintomas mais prevalentes nos pacientes com coinfecção foram dispneia, febre, desconforto respiratório, presença de tiragens e crepitações à ausculta pulmonar, igualmente observados nos pacientes que tiveram apenas infecção por Sars-CoV-2. No grupo com coinfecção viral foi observado maior tempo em oxigenoterapia, maior taxa de alterações radiológicas e/ou hematológicas, maior tempo de internação e necessidade de unidade de terapia intensiva. Conclui-se que a infecção pelo Sars-CoV-2 em crianças é de extrema importância e que a taxa de coinfecção com outros vírus apresenta diferentes prevalências a depender da região estudada; pela baixa taxa de coinfecção encontrada em nossa casuística não foi possível realizar análise estatística mais detalhada, sendo necessários estudos maiores e com testagem viral mais ampla para melhor definir o impacto da coinfecção do Sars-CoV-2 com outros vírus na epidemiologia e na clínica desses pacientes.
Rate of viral co-infection in children and adolescents hospitalized with Sars-CoV-2: clinical and epidemiological characteristics.
Keywords: Sars-CoV-2; Coinfecção viral; Pediatria; COVID-19 (Doença); Pediatrics; Pediatrics